Rancang Bangun Jadwal Waktu Sholat Menggunakan Panel Led Matrix P10 Berbasis Arduino Uno Sebagai Media Informasi Di Surau Al-Muhtadin - Allkadri, Syarif Ishak; Suwanda, Ivan; Sonia, Etika (entries, 2025)
ABSTRACT Followers of the Islamic religion believe in the obligation to pray 5 times a day, at which time they are carried out. For this reason, knowing the 5 daily prayer times, namely dawn, midday, Asr, Maghrib and Isha is very important for every follower of the Islamic religion in carrying out the 5 daily prayers correctly and as well as possible. For this reason, it is very important to have a prayer schedule. Nowadays, in many mosques and houses, there are usually calendars and displays of eternal prayer times, but the display is so small that it cannot be seen from a very long distance. So many people want to provide information with various interesting media such as prayer time schedules and much more. This makes it easy for people to recognize the device with various other supporting devices. Replacing data text and assembling a prayer time schedule display using a P10 LED matrix panel is currently still relatively difficult for ordinary people. That's why a prayer time schedule was created with the help of Arduino Uno. Prayer schedule information can be updated via Android cellphone with Bluetooth communication. On Android phones, an application can send characters to change the text printed on the P10 led matrix panel. The information sent will be received in the Bluetooth module and processed in the microcontroller and then displayed on the panel. This tool is expected to make it easier for users to view prayer time schedules and change information on prayer time schedules via an Android cellphone with a Bluetooth connection. The aim of this research is that the use of technology from Android and Arduino can be collaborated to make changing prayer time schedule data on the P10 panel faster. and it's easy now. Keywords: Prayer Times Schedule, Led Matrix Panel p10, Arduino uno